Analisis kualitas laporan keuangan dan dampaknya terhadap keputusan investasi - Ramadhani, Faidatul Fitriyah (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the quality of financial statements and their impact on investment decision-making. Reliable, relevant, and transparent financial statements are considered key factors in attracting investors to make investments. The research employs a quantitative approach using secondary data from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) over the past five years. This study evaluates dimensions of financial statement quality, such as relevance, reliability, and consistency, and their impact on investment decision indicators, including asset growth, return on investment, and market value. The analysis results reveal that high-quality financial statements have a significant positive effect on investment decisions. Moreover, transparency in financial information plays a crucial role in building investor trust. These findings have implications for financial managers to enhance the quality of financial statements to support optimal investment decision-making. The study also provides insights for regulators to strengthen policies for more accountable financial reporting.